STUDENTS’ INDEPENDENT LEARNING IN GROUP WORK ACTIVITIES - Khoirul Anwar (DIDAKTIKA, 2014)
This study is to find out the students' preferences in independent learning after the implementation of group work activities at the sixth semester students of English Education Department of University of Muhammadiyah Gresik. The number of eighteen students are provided by group work activities (combined by a Lesson Study model) in the subject of Classroom Action Research. After that they are given a questionnaire about the preferences of independent learning with five categories namely self-confidence, discipline, initiative, responsibility, and motivation. Data show that there are positive responses of the students' preferences in terms of better self-confidence, higher discipline, superior initiative, recovered responsibility, and better motivation in learning.